ANALYSIS OF COMPENSATION, COMPETENCE, SELF EFFICACY AND JOB SATISFACTION ON NURSE PERFORMANCE - Effendi, Raden Gunawan (Program Doktor Ilmu Ekonomi, 2021)
The purpose of this study was to examine the effect of compensation,competence and self-efficacy on job satisfaction and its impact on theperformance of inpatient nurses in the Patut Patuh Patju Hospital.Collecting data using the census method with a number of respondents63 nurses. Primary data collection was carried out by distributingquestionnaires which were prepared using a Likert scale and thenanalyzed using the Structural Equation Model (SEM) with the PartialLeast Square (PLS) program. The results showed that the compensationvariable had a significant effect on job satisfaction and nurseperformance. The competency variable has no significant effect on jobsatisfaction, but has a significant effect on nurse performance. The selfefficacyvariable has no significant effect on job satisfaction. but has asignificant effect on nurse performance. Job satisfaction variable has asignificant effect on nurse performance. The conclusion of this study isthat the variables of compensation, competence, self- efficacy, and jobsatisfaction have a significant effect on the performance of inpatientnurses in the Patut Patuh Patju Hospital Gerung.Keywords: compensation; competence; job satisfaction; nurseperformance; self efficacy